N.R. Ayupova - N.R. Ayupova (Минералогия)
Paleozoic siliceous-ferruginous oxide sedimentary rocks of the Urals massive sulfide deposits contain well-preserved textural and structural evidence indicating the role of microorganisms in their formation. Filamentous, rod-shaped, spherical and tubular micron-scale bacterial forms mineralized with hematite, hematite-siliceous and siliceous material are described. The filamentous forms are morphologically dominant. Authigenic apatite, Mn-calcite, Ti oxides, illite and rare earth minerals (phosphates and carbonates) are constantly associated with bacteriomorphic structures. The structures of fossil bacteria based on their size, shape, cell division, distribution in colonies and comparison with ferruginous sediments of modern hydrothermal systems and massive sulfide deposits worldwide indicate that they correspond to mineralized stalks of iron bacteria Leptothrix ochracea and Gallionella ferruginea, coccoidal forms and sulfur-oxidizing Thiobacillus Ferrooxidans and giant Beggiatoa-like organisms. These observations indicate bacterial biocatalysis in the processes of halmyrolysis of sulfides and hyaloclasts during the formation of iron oxide deposits.